Survey of Linux-Based Free Software Tools for Electrical and Computer Engineering (ECE) - Wajid, Dr. Bilal; Iqbal, Hasan; Jamil, Momina; Anwar, Ali; Rafique, Hafsa; Rafique, Insha (Innovative Computing Review, 2025)
The undergraduate program in Electrical and Computer Engineering (ECE) is a four-year curriculum where students work on several software to complete their coursework. These tools are accessible to students in universities where they spend several hours completing their assignments, a process not doable under the COVID-19 global lockdown. Hence, students either (i) access their university labs remotely via virtual private networks, or in the absence of remote access (sadly) (ii) resort to using pirated software, or (regretfully) (iii) are deprived of hands-on knowledge of the course. In this (post) COVID-19 era, educators are required to adopt teaching pedagogy in order to ensure maximum delivery of their course material. In an attempt to facilitate experimental learning, this effort provides a detailed survey of Linux-based tools coupled with their corresponding coursework within ECE with the hope that the content provided in this paper would be of some relief to students and teachers engaged in ECE education globally.